Skuteczność procesu motywacji pracowników w organizacji: The effectiveness of the process of motivation in an organization - Ciekanowski, Zbigniew (Management and Administration Journal, 2021)
This article emphasized the role of motivation as the key factor in the management of a company. Motivation is a process aimed at increasing work efficiency and effectiveness. Its application depends on employees’ preferences and may take either a financial or non financial form such as promotion, increased independence or by allocation of more responsible tasks. The effectiveness of a non financial motivation depends on to what extent it satisfies the employees’ needs. The role of a good manager is the skilful use of material and non material measures in order to encourage employees to work more effectively.